Efektivitas Disiplin dan Kecerdasan Afektif Perspektif Taksonomi Bloom Melalui Penerapan Tujuh Sunnah Harian SAW di Lembaga Pendidikan Muhamammdiyah - Eka Rachma Kurniasi (MUADDIB Jurnal Kependidikan dan Keislaman, 2022)
Discipline is a very important aspect and becomes a part of character. Discipline in learning can support other abilities in student learning outcomes. Likewise affective intelligence. Bloom stated that the realm that must also be developed in students is affective. The importance of these two things, of course, must be stimulated in their development in schools. One of them is through the application of the seven daily sunnahs of the Prophet Muhammad. The seven sunnahs are congregational prayers, Duha matters, almsgiving, istigfar, reading the Qur'an, praying at night, keeping ablution. This study aims to see the effectiveness of discipline and affective intelligence from the perspective of Bloom's Taxonomy through the application of the seven daily sunnahs of the Prophet Muhammad in Muhammadiyah Educational Institutions. This study uses a qualitative approach to formative evaluation with the CIPP model (context, input, process, product). Data collection techniques used observation sheet instruments, interview guides, discipline questionnaires and affective intelligence, documentation studies. Test the validity of the data by triangulation. Meanwhile, data analysis used data analysis, data reduction, data presentation, and data evaluation. The research sites are STKIP Muhammadiyah Bangka Belitung Elementary School, Muhammadiyah Middle School Pangkalpinang, and Muhammadiyah Toboali High School. The research subjects were students, teachers, and the STKIP Muhammadiyah Bangka Belitung Elementary School, Pangkalpinang Muhammadiyah Middle School, and Toboali Muhammadiyah High School who applied the seven daily sunnahs of the Prophet SAW. Subjects were selected by purposive technique.The results showed that overall at the elementary, junior high, and high school levels, student discipline increased with the application of these seven daily sunnahs. This increase is experienced by students gradually over a period of one to three academic years. The results of the next study stated that the affective intelligence of the Bloom's Taxonomy perspective of students at the elementary, junior high, and high school levels could be optimized through the application of the seven daily sunnah.